Estudo de azaçúcares como inibidores de Glge, uma maltosiltransferase de Mycobacterium tuberculosis, por meio de docking molecular e da avaliação de interações moleculares - Pedroso, Sofia Dallasta (Universidade Federal de São Carlos, 2023)
Tuberculosis is still a worrying disease around the world, especially in low- and middle-income countries. Current treatment for tuberculosis involves a combination of antibiotics, however, it is often ineffective due to drug resistance and the difficulty of completely eliminating the disease-causing bacteria, namely Mycobacterium tuberculosis. In this context, the use of molecular docking is a promising tool in the development of new drugs for the treatment of tuberculosis. Molecular docking consists of the computational analysis of the fitting of a drug candidate molecule with bacterial proteins, thus allowing the identification of promising compounds and optimizing their effectiveness. Its use aims to accelerate the development of new drugs, improving the effectiveness of tuberculosis treatment. In this context, azasugars have been studied as possible drugs for the treatment of tuberculosis, due to their ability to inhibit the enzyme maltosyltransferase (GlgE), essential for the survival of Mycobacterium tuberculosis. Furthermore, azasugars have low toxicity and high selectivity, increasing their therapeutic efficacy. In this sense, in the present work we describe the study of three series of azasugars with the aim of evaluating their potential as anti-tuberculosis drugs targeting GlgE. The results point to a compound, called A532 in this study, as a substance of pharmacological interest for this purpose, due to its favorable interaction with the active site of the enzyme, explained by the existence of a network of π interactions and hydrogen bonds. Furthermore, the results presented provide further information about the structure of possible GlgE-inhibiting azasugars and their relationship with the residues that make up its active site.
Study of azasugars as inhibitors of Glge, a maltosyltransferase from Mycobacterium tuberculosis, through molecular docking and evaluation of molecular interactions
Keywords: Tuberculose; GlgE; Maltosiltransferase; Docking; CIENCIAS BIOLOGICAS::FARMACOLOGIA::FARMACOLOGIA BIOQUIMICA E MOLECULAR